On mystery, ineffability, silence, and musical symbolism - Wuidar, Laurence 1978- (New York Bloomsbury Academic, 2021)
Introduction, or first steps into the text -- The Christian -- The Prophet and the Saint -- Christ -- The Father.
"Laurence Wuidar collects together numerous examples of Augustine's musical imagery in action, reconstructing the linguistic laboratory and the hermeneutics in which he worked. Sensitive and poetical, this volume is a reminder that the metaphor of music-a long-time means of knowledge within the discourses of theology-can give access not only to human interiority, therefore serving as a key to philosophical anthropology, but actually allow the human mind to achieve proximity to the divine mind and the mystery of the divine incarnation Any investigation of Augustine's use of musical symbolism is naturally also an investigation of the gnoseological value of music, and of its creative potential in the hands of such a writer. Composed by one of Europe's leading musicologists, now engaging an English-speaking audience for the first time, this book is a candid exploration of Wuidar's expertise. Drawing on her long knowledge of music and the occult, from antiquity to modernity, Wuidar particularly focuses upon Augustine's working methods while resufing to be distracted by questions of faith or morality. The result is an open and at times frightening vista on the powers that be, and our complex need to commune with them"--
"This book was originally published in 2014 by Mimesis Edizioni, Milan, as La simbologia musicale nei commenti ai Salmi di Agostino"--Translator's note
Includes bibliographical references and index
Keywords: Augustine -- of Hippo, Saint -- 354-430 -- Knowledge -- Music; Augustine -- of Hippo, Saint -- 354-430 -- Criticism and interpretation; Music -- Religious aspects -- Christianity